Hashimoto's Thyroiditis and Kikuchi's Disease: Presentation of a Case and Review of the Literature. (28th November 2012) - Saratziotis, Athanasios; Karakousis, Konstantinos; Tzika, Kelly; Oikonomou, Katerina G.; Vlachostergios, Panagiotis J.
Abstract : We report the case of a 19-year-old woman with a history of Hashimoto's thyroiditis who presented with tender right anterior cervical lymphadenopathy and fever. Workup for infectious, autoimmune, and malignant causes was unremarkable. Surgical removal of cervical lymph nodes after detailed magnetic resonance (MR) imaging disclosed necrotizing lymphadenitis, also known as Kikuchi's disease (KD). The patient was treated with a short-term course of steroids, due to the onset of pancytopenia and borderline antiphospholipid antibodies combined with increased anti-thyroglobulin (anti-TG) titers. Despite being a diagnosis of exclusion, KD should be included in the differential of such patients, particularly in cases of previous or concurrent autoimmune diseases such as Hashimoto's thyroiditis, which necessitate a long-term follow-up.